Pharmaceutical biotechnology : drug discovery and clinical applications - Kayser, Oliver; Warzecha, Heribert; Wiley InterScience (Online service) (Hoboken : John Wiley & Sons, 2012)
"This second edition of a very successful book is thoroughly updated with existing chapters completely rewritten while the content has more than doubled from 16 to 36 chapters. As with the first edition, the focus is on industrial pharmaceutical research, written by a team of industry experts from around the world, while quality and safety management, drug approval and regulation, patenting issues, and biotechnology fundamentals are also covered. In addition, this new edition now not only includes biotech drug development but also the use of biopharmaceuticals in diagnostics and vaccinations."--Provided by publisher.
11 Drug Approval in the European Union and United States.
Previous edition: 2004.
Includes bibliographical references and index.
Print version record.
Keywords: Pharmaceutical biotechnology; Pharmaceutical biotechnology; Pharmazeutische Technologie; Biotechnologie; Bioteknik; Electronic books